2017
DOI: 10.1007/s00213-017-4684-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of serotonin transporters disrupts the enhancement of fear memory extinction by 3,4-methylenedioxymethamphetamine (MDMA)

Abstract: Rationale 3,4-methylenedioxymethamphetamine (MDMA) persistently improves symptoms of post-traumatic stress disorder (PTSD) when combined with psychotherapy. Studies in rodents suggest that these effects can be attributed to enhancement of fear memory extinction. Therefore, MDMA may improve the effects of exposure-based therapy for PTSD; particularly in treatment-resistant patients. However, given MDMA's broad pharmacological profile, further investigation is warranted before moving to a complex clinical popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 77 publications
5
65
1
1
Order By: Relevance
“…Potential mechanisms underlying the observed therapeutic effects of MDMA-assisted psychotherapy include acute changes in brain activity associated with emotional memory processing (Carhart-Harris et al 2015 ; Gamma et al 2000 ), which may reduce distress when facing traumatic memories, an increase in emotional empathy for self and others, and greater self-compassion (Baggott et al 2015 , 2016 ; Bedi et al 2010 , 2014 ; Schmid et al 2014 ). Another proposed mechanism is enhancement of fear extinction (Feduccia and Mithoefer 2018 ) suggested by nonclinical studies indicating that MDMA can enhance this process in rodents (Young et al 2015 ; Young et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Potential mechanisms underlying the observed therapeutic effects of MDMA-assisted psychotherapy include acute changes in brain activity associated with emotional memory processing (Carhart-Harris et al 2015 ; Gamma et al 2000 ), which may reduce distress when facing traumatic memories, an increase in emotional empathy for self and others, and greater self-compassion (Baggott et al 2015 , 2016 ; Bedi et al 2010 , 2014 ; Schmid et al 2014 ). Another proposed mechanism is enhancement of fear extinction (Feduccia and Mithoefer 2018 ) suggested by nonclinical studies indicating that MDMA can enhance this process in rodents (Young et al 2015 ; Young et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…This may have been due to the locomotor stimulant effect of the drug, or could indicate an effect similar to that of benzodiazepines or alcohol which can acutely decrease fear responses but do not facilitate lasting extinction (Bouton et al, 1990). Regardless, previous studies have demonstrated that fear behavior during training is irrelevant to the lasting extinction improvements by SR -MDMA (Young et al, 2017, 2015).…”
Section: Discussionmentioning
confidence: 94%
“…Clinical studies have found that the majority of SR -MDMA’s subjective effects can be attributed to release of 5-HT (Liechti et al, 2000a), NE (Hysek et al, 2012, 2011), and activation of 5-HT2A receptors (Liechti et al, 2000b). Each of these factors is also necessary for the facilitative effect of SR -MDMA on fear extinction in mice (Young et al, 2017), and 5-HT2A activation is necessary for the increased affiliative behaviors in SR -MDMA treated squirrel monkeys (Pitts et al, 2017). Thus, as a racemic mixture, S -MDMA may provide the necessary 5-HT and NE release, while R -MDMA provides the necessary 5-HT2A activation.…”
Section: Discussionmentioning
confidence: 99%
“…Brièvement, les patients ESPT présentent une hypermnésie de leurs souvenirs traumatiques, et une capacité réduite à éteindre la peur qui est associée au souvenir traumatique. Il semblerait que l'aptitude de la MDMA à favoriser l'extinction soit médiée par la sérotonine et les récepteurs 5-HT 2A , car leur inhibition limite son efficacité (Young et al, 2017). Les effets de cette drogue sur les neurotrophines ne sont pas clairement établis du fait de la variabilité des protocoles et des doses, d'autant plus que les fortes doses et/ou l'administration répétée sont neurotoxiques (Dunlap et al, 2018).…”
Section: 4-méthylènedioxyméthamphétamine Et Neurotrophinesunclassified